Endocytosis induction by high-pulsed magnetic fields to overcome cell membrane barrier and improve chemotherapy efficiency. (3rd July 2021) - Yadegari Dehkordi, Sajedeh; Firoozabadi, Seyed Mohammad; Forouzandeh Moghadam, Mehdi; Shankayi, Zeinab
ABSTRACT: Cell membrane acts as a barrier to the entry of impermeable drugs into cells. Recent studies have suggested that using magnetic fields can enable molecules to overcome the cell membrane barrier. However, the mechanism of membrane permeabilization remains unclear. Therefore, we evaluated the increases in bleomycin (CT) uptake, a non-permanent chemotherapy agent, using high-pulsed magnetic fields and investigated whether endocytosis was involved in the process. This study exposed MCF-7 cells to magnetic fields (2.2 T strength, different number of 28 and 56 pulses, and frequency of 1 and 10 Hz) in order to investigate whether this approach could promote the cell-killing efficiency of bleomycin. The involvement of endocytosis as a possible mechanism was tested by exposing cells to three endocytosis inhibitors, namely chlorpromazine, genistein, and amiloride. Our results illustrated that magnetic fields, depending on their conditions, could induce different endocytosis pathways. In such conditions as 10 Hz-28 pulses, 10 Hz-56 pulses, and 1 Hz-56 pulse, clathrin-mediated endocytosis was observed. Moreover, macropinocytosis was induced by the 10 Hz magnetic field and caveolae-mediated endocytosis occurred in all the magnetic field conditions. The findings imply that high-pulsed magnetic fields generate different endocytosis pathways in the MCF-7 cells, thus increasing the efficiency of chemotherapy agents.